Connection between academic emotions in situ and retention in the physics track: applying experience sampling method - Sanna Lehtamo; Kalle Juuti; Janna Inkinen; Jari Lavonen (SpringerOpen, 2018)
Abstract Background There is a lack of students enrolling in upper secondary school physics courses. In addition, many students discontinue the physics track, causing a lack of applicants for university-level science, technology, engineering and mathematics (STEM) programmes. The aim of this research was to determine if it is possible to find a connection between academic emotions in situ and physics track retention at the end of the first year of upper secondary school using phone-delivered experience sampling method. We applied experience sampling delivered by phone to one group of students in one school. The sample comprised 36 first-year upper secondary school students (median age 16) who enrolled in the last physics course of the first year. Students' academic emotions during science learning situations were measured using phones three times during each of four physics lessons. Results The logistic regression analysis showed that lack of stress predicted retention in the physics track. Conclusions Via questionnaires delivered by phone, it is possible to capture students' academic emotions in situ, information on which may help teachers to support students emotionally during their physics studies. In addition, reflecting their situational academic emotions, students could perhaps make better-informed decisions concerning their studies in STEM subjects.